KARAKTERISTK IBU HAMIL DALAM PEMANFAATAN BUKU KIA SEBAGAI MEDIA KIE - Isasih, Widani Darma; Inayati, Rizqa (IMJ (Indonesian Midwifery Journal), 2023)
The MCH handbook is a guidebook owned by pregnant women which contains information and documents for recording mothers and children as well as KIE media. In Lombok Regency, it was found that the utilization of the MCH handbook as an IEC medium for pregnant women was still not optimal. Factors that may influence the use of Maternal and Child Health (MCH) books as IEC media for pregnant women are the characteristics of pregnant women. This research is a quantitative study with a cross-sectional study design. The population is 403 pregnant women in North Lombok district. The research sample of 107 people was taken by accidental sampling method, interviewed with a questionnaire that had been tested for validity and reliability, data processing used the Chi-Square test. The results of the study found that most of the respondents were aged <20 years and >35 years, namely 79 pregnant women (73.8%). 62 pregnant women (57.9%) have high school education level. Most of them had a history of multigravida pregnancies (2-3rd pregnancies) as many as 73 people (68.2%) and the majority used MCH books as KIE media, namely 101 pregnant women (94.3%). In addition, the P value for each variable is smaller than 0.05, namely sig age 0.024 <0.05, education level 0.040 <0.05, and educational history 0.013 <0.05. This shows that there is a significant relationship between age, education level and history of pregnancy with the utilization of the MCH handbook for pregnant women in North Lombok District.